Radiology as an aid to diagnosis in lung disease. Issue 1092 (17th August 2016) - Ellis, Stephen; Aziz, Zelena
Abstract: A great deal has changed in the imaging of chest diseases over the last 90 years. The plain chest radiograph has gone through numerous improvements and continues to be the front-line investigative technique with the mainstream adoption of digital imaging opening the doors to more advances in imaging efficacy and computer-aided diagnostics. The main change is in the advent and dramatic advances in CT, in some instances superseding the chest X-ray (CXR) as the first-line imaging investigation, not entirely to the authors' liking, and providing in vivo morphological data to aid a more specific diagnosis. However, in our view, there is a danger that the improvement in diagnostic imaging is starting to undermine clinical diagnostic acumen and that there is an increasing reliance on imaging that in the long run may not be advantageous to patient management.